关丹华人社会的抗日运动与日据时期: 1937-1948 - 高, 嘉雯 (2023)
近几十年来，马来西亚日据时期的华人社会研究一直是国内外的研究热点。鉴于以 往研究多着重在大的地域范围，即马来亚与新加坡。本文缩小了范围，选取关丹为研究个 案，深入剖析华社于日据时期的历史事实。虽然范围缩小至关丹一角，不过却能以小见大， 建构关丹华社在日据时期的具体轮廓，并增补马来亚日据时期华社历史的空白之处。研究 内容涉及关丹华社援中抗日、逃灾避难、皇民化及高压生活与地下抗日等历史阶段。作为 一项以史学为主的研究，本文使用了一手材料，如手稿、画稿与遗物等进行论述。此外， 笔者亦对八名经历二战的长者（以及一名对该过往有一定研究的长者）进行了深度访谈， 并实地考察了相关地点。这是希望能够以今溯往，在一切尚未消失前，记录下那个悲惨且 动荡的时代。 全文共六章，第一章主要交代研究背景，包括研究目的、问题与方法等；第二章是 关丹华社战前的发展状况，也涉及关丹华社的南移历史；第三章与第四章是论述核心，即 将史料、访谈与实地的调查结合，推出日据时期关丹华社的整体情况；第五章是关丹华社 的抵抗及战后的恢复情况；第六章是全篇的总结，即结论与展望部分。本文研究发现，在 较少研究成果并缺乏相关材料的情况下，日据时期关丹华社的历史面目，已越发稀缺与模 糊。纵使理出了整体情况，但其中仍有许多细节，需在挖掘更多的资料后，予以补充。在 此希望，通过研究能对马来西亚华社的历史事实，特别是关丹华社的历史记忆，提供一点 启示。同时，也希望此文能对往后的相关研究，提供些许的借鉴，以寻求这段历史更细致、 多面与深入的一面。In recent decades, the study of Chinese society during the Japanese occupation of Malaya has been an international research hotspot. According to previous studies, most of them focused on large geographical areas, namely Malaya and Singapore. This study narrows down the scope and Kuantan is selected as a case study to analyse the historical facts of the Chinese society during the Japanese occupation. Although the scope is focus on Kuantan, this study helps to put the pieces together and review the history of the Chinese society during the Japanese occupation of Malaya. This research involves the historical stages of the Kuantan Chinese society from assisting China resist Japan, escaping from the city, experiencing japanization and high-pressure life, to fighting against Japan.As a historical research,this study uses primary sources such as manuscripts, drawings and relics for research.In addition, it also conducted in-depth interviews with eight elders who lived through World War II (and one elder who had done some research on this past), as well as field trips to relevant locations. It is hoped that this research will be able to document that tragic and turbulent era before it all fades away. There are 6 chapters in this dissertation. Chapter 1 mainly explains the research background, including the research purpose, problems and methods; Chapter 2 is the development of the Kuantan Chinese society before the war, involving their migration history; Chapters 3 and 4 are the core of the research, combining historical materials, interviews and field investigations to reveal the overall situation of the Kuantan Chinese society during the Japanese occupation; Chapter 5 is the recovery of the Kuantan Chinese society after the war; Chapter 6 is the summary of the paper, namely the conclusion and prospect. With few research results and lack of relevant materials, this paper finds that the historical side of the Kuantan Chinese society during the Japanese occupation has become more and more scarce and vague. Even though the overall situation has been clarified, there are still many details that need to be supplemented. It is hoped that this study can provide enlightenment to the historical facts of the Chinese society in Malaysia, especially the historical memory of the Kuantan Chinese society. At the same time, this paper hopes to provide some reference for future related research, to find out more detailed, multifaceted and in-depth side of this history.